The activity of a developmentally regulated cysteine proteinase is required for cyst wall formation in the primitive eukaryote Giardia lamblia - Touz, Maria Carolina (2002)
Giardia is an intestinal parasite that belongs to the earliest diverging branch of the eukaryotic lineage of descent. Giardia undergoes adaptation for survival outside the host's intestine by differentiating into infective cysts. Encystation involves the synthesis and transport of cyst wall constituents to the plasma membrane for release and extracellular organization. Nevertheless, little is known about the molecular events related to cyst wall biogenesis in Giardia. Among the components of the cyst wall there are two proteins that we have previously identified and characterized: CWP1 (26 kDa) and CWP2 (39 kDa). Expression of these proteins is coordinately induced, and both concentrated within encystation-specific secretory vesicles before their extracellular polymerization. Although highly similar to each other at the amino terminus, CWP2 includes a COOH-terminal 121-amino acid extension. Here, we show that this extension, rich in basic residues, is cleaved from CWP2 before cyst wall formation by an intracellular cysteine proteinase activity, which is induced during encystation like CWPs. Specific inhibitors prevent release of cyst wall materials, abolishing cyst wall formation. We also report the purification, cloning, and characterization of the encystation-specific cysteine proteinase responsible for the proteolytic processing of CWP2, which is homologue to lysosomal cathepsin C. Encystation-specific cysteine proteinase ESCP possesses unique characteristics compared with cathepsins from higher eukaryotes, such as a transmembrane domain and a short cytoplasmic tail. These features make this enzyme the most divergent cathepsin C identified to date and provide new insights regarding cyst wall formation in Giardia.